Design of Green House Information System Using Virtual Reality - Suhendi Suhendi; Lu’lu-Ul Muksin; Reza Maulana; F Rachmat Kautsar; Fajar Ainur Ridhwan (International Journal of Business and Management Technology in Society, 2023)
Purpose – The aim of this research is to create a hydroponic greenhouse that can be viewed virtually. Methodology – The research method used is the multimedia development life cycle (MDLC) with stages of concept, design, asset creation, asset assembly, internal testing, and distribution for limited testing. Findings – The findings obtained were successful in creating a hydroponic greenhouse application. Originality – The originality of this research is the application of hydroponic greenhouses that can be enjoyed virtually by students and the public. Research limitations – The research limitations in this study are the VRBox tool which is still limited because it still uses Google Cardboard in terms of VR features. Practical Implications – This research is expected to have implications for application in schools to view hydroponic greenhouse rooms virtually. Social Implications – The social implications of this research are that it is useful for students and the community to see hydroponics virtually.